Palaeontology with SKA precursors: observations of fossil radio plasmas in galaxy clusters - Duchesne, Stefan W. (Curtin University, 2021)
The population of diffuse, non-thermal radio sources in galaxy clusters presents an ever-increasing insight into both cosmic magnetic fields and structure formation at the largest scales in the Universe. Understanding the underlying physical processes generating the radio emission observed is a key science goal for low-frequency radio telescopes. This research has improved the statistics of these diffuse radio sources and highlighted a potential link between them and an underlying fossil particle population in clusters.